Association of Osteoarthritis With Changes in Structural Neuroimaging Markers Over Time Among Non-demented Older Adults - Wu, Lichuang; Wang, Xiang; Ye, Yiheng; Liu, Cailong (Frontiers in Aging Neuroscience, 2021)
Objective: Although emerging evidence suggests that both osteoarthritis (OA) and brain atrophy (as assessed by structural neuroimaging markers) are associated with risk of dementia, little is known about the association between OA and structural neuroimaging markers. This study aimed to examine the association of OA with changes in structural neuroimaging markers among non-demented older people. Methods: We examined the cross-sectional and longitudinal associations between OA and structural neuroimaging markers (hippocampal volume, entorhinal volume, ventricular volume and volume of gray matter of the whole brain) among non-demented older people. We categorized our participants as those without OA (OA-) and those with OA (OA+). At baseline, we included 1281 non-demented older adults, including 1050 without OA and 231 with OA. Results: In the cross-sectional analysis, we did not observe any significant difference in structural neuroimaging markers between two OA group. In the longitudinal analysis, we found that compared to participants without OA, those with OA showed a steeper decline in volumes of gray matter of the whole brain among non-demented older adults. Conclusions: OA was associated with a steeper decline in volumes of gray matter of the whole brain over time among non-demented older people.